Renormalized Energy with Vortices Pinning Effect (Journal of Partial Differential Equations, 2020)
This paper is a continuation of the previous paper in the Journal of Partial Differential Equations [1]. We derive in this paper the renormalized energy to further determine the locations of vortices in some case for the variational problem related to the superconducting thin films having variable thickness.
Keywords: Renormalized energy; superconductivity; vortices; pinning mechanism